(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of good governance (X1), transformational leadership style (X2), simultaneously or partially on the performance of officials in the government of North Gorontalo District. As well as the influence of Good governance (X1) on transformational leadership style (X2), the population in this study were State Civil Servants who held structural positions in seven Regional Work Units (SKPD) in the Regional Government of Gorontalo Utara Regency, amounting to 63 people, data collection principal through a list of questions that were tested on the instrument, namely the validity test and reliability test for each question item contained in the list of questions. The analytical method used is the Structural Equation Model PLS by using the Smart PLS.3.0 application. The results showed that, Good governance (X1), has a positive and significant effect on the performance of the apparatus in the North Gorontalo District government. The effect is low with the magnitude of the effect of 0.333 or 33.3%. The transformational leadership style (X2) has a significant and positive effect on the performance of the apparatus in the North Gorontalo district government. The effect is moderate with a large influence of 0.467 or 46.7%. The results showed that, Good governance (X1), has a positive and significant effect on transformational leadership style (X2) in the government of North Gorontalo District. The influence is high, with the magnitude of the effect of 0.712 or 71.2%. Good governance (X1) and transformational leadership style (X2) simultaneously have a positive and significant effect on the performance of the apparatus (Y) in the government of North Gorontalo District. The effect is moderate with the magnitude of the effect of 0.665 or 66.5%.